An exploration of the porridge tradition in Southern Sri Lankan culture - Piyoda Darmasiri Wijesekara (Journal of Ethnic Foods)
Abstract The concept of porridge developed independently across diverse culinary customs globally, as a simple, nutritious, and economical meal option. It is a cooked cereal dish with a semi-solid consistency. Porridge is known as “Congee”, “Kanji” and “Dakjuk” in specific subcultures, while quinoa, oats, corn, rice and millet are widely used cereals for porridges worldwide. However, in the Sri Lankan context, the concept of porridge has gained prominence, serving as a culinary delight and a medicinal remedy for common ailments. The main objective of this study was to identify traditional food practices in Southern Sri Lankan heritage, focusing on the ingredients and preparation methods of porridges, to ensure the preservation and transmission of traditional knowledge. This study was conducted through observations and in-depth discussions with a selected group of elderly individuals within the Galle district of Sri Lanka. It became apparent that the primary constituents of many porridges were sourced from various botanical parts such as green leaves, rhizomes, bulbs, trunks or grains. Leaves (57%) are the most used plant part in porridge making. Thick coconut milk, which is abundantly available, is commonly incorporated to enhance the richness and creaminess of many porridge varieties. Unlike cereal porridge, herbal porridge is not boiled for an extended period to preserve the nutrients in the herbs. Further, Sri Lankan porridges are in two distinct flavor profiles. Pepper, ginger, and garlic are added, to enhance the savory flavor profile, contributing to a more robust and aromatic taste, often described as spicy, pungent, and warming. Meanwhile, a variety of porridges are added spices, such as cinnamon, cardamom, cloves and sugar or jaggery to enhance the sweet flavor profile. Accordingly, it is evident that Sri Lankan porridge culture features a diverse array of porridges crafted from locally sourced ingredients. This research underscores the cultural and sustainable significance of Southern Sri Lankan porridges, promoting their potential for health, food security, and cultural preservation.